Machinability of advanced materials - Davim, J. Paulo (London : ISTE ; Hoboken, NJ : Wiley, 2014)
Machinability of Advanced Materials addresses the level of difficulty involved in machining a material, or multiple materials, with the appropriate tooling and cutting parameters. A variety of factors determine a material's machinability, including tool life rate, cutting forces and power consumption, surface integrity, limiting rate of metal removal, and chip shape. These topics, among others, and multiple examples comprise this research resource for engineering students, academics, and practitioners.
4.2.1. Metallography-microstructural examination4.2.2. Mechanical tests; 4.2.3. Machining procedures; 4.2.4. Total drilling force; 4.2.5. Tool life criteria; 4.3. Results; 4.3.1. Microstructures; 4.3.2. Hardness and tensile properties; 4.3.3. Machining behavior; 4.4. Discussion; 4.5. Conclusions; 4.6. Acknowledgments; 4.7. Bibliography; Chapter 5. The Machinability of Hard Materials -- A Review; 5.1. Introduction; 5.1.1. Definition of hard machining; 5.1.2. Application of hard machining processes; 5.2. Cutting tools; 5.2.1. Ceramics; 5.2.2. Cubic boron nitride (CBN); 5.3. Wiper technology.
5.4. Machinability.
Print version record.
Keywords: Building materials; Machine design; Materials -- Mechanical properties; Building materials; Machine design; Materials -- Mechanical properties; TECHNOLOGY & ENGINEERING -- Mechanical; Building materials; Machine design; Materials -- Mechanical properties; Electronic books